Antibacterial profiles of bacterial isolates from maternity ward hospital beds at Bubulo health centre IV, A cross- sectional study. - Manowa, Daniel; Mabonga, Mr. Habert; Kasozi, James (Student’s Journal of Health Research Africa, 2025)
Background: Healthcare-associated infections (HAIs) remain a major challenge in maternity wards, particularly in low-resource settings like Uganda. This study investigated the antibacterial profiles of bacterial isolates from maternity ward bed surfaces at Bubulo Health Centre IV, Manafwa District, to address knowledge gaps and inform infection control practices. Methodology: A cross-sectional, laboratory-based analytical study was conducted over three months, during which 60 swab samples were collected from high-touch points on maternity beds, including mattress covers, bed rails, and headboards. Samples were cultured on selective media, and bacterial isolates were identified through Gram staining and biochemical tests. Antibacterial susceptibility testing was performed using the Kirby-Bauer disk diffusion method in accordance with CLSI guidelines. Results: The study identified five bacterial species: Staphylococcus aureus (33.3%), Escherichia coli (20%), Enterococcus spp. (16.7%), Klebsiella pneumoniae (15%), and Proteus spp. (15%). Gram-positive and Gram-negative bacteria were equally represented (50% each). Antibacterial susceptibility testing revealed that Gram-positive isolates were highly sensitive to Vancomycin (100%) and Gentamicin (80–90%), with 25% of S. aureus isolates resistant to Oxacillin, suggesting possible MRSA strains. Gram-negative isolates showed high sensitivity to Ciprofloxacin (88–83%) and Ceftriaxone (77–75%), but moderate to high resistance to Ampicillin (33–66%) and Co-trimoxazole (33%). These findings indicate the presence of multidrug-resistant organisms on maternity bed surfaces, highlighting the risk of nosocomial infections. Conclusion: Maternity bed surfaces at Bubulo Health Centre IV are contaminated with clinically significant bacteria, including multidrug-resistant strains. The study underscores the urgent need for stringent IPC practices, routine environmental surveillance, rational antibiotic use, and targeted cleaning and disinfection strategies to safeguard maternal and neonatal health. Recommendation: Strengthen national infection prevention guidelines, ensure strict cleaning and disinfecting practices in health facilities, provide regular staff training and supplies, and promote public awareness on personal and environmental hygiene